Regional Disparities in Social Development: Evidence from States and Union Territories of India. (March 2019) - Kumar, Naresh; Rani, Ritu
The present study examines the regional disparities in social development in India by using social development index (SDI). The study used census-based data of 2011 including 28 states and seven union territories (UTs) of India. The study ends by ranking of states and UTs on the basis of development index consisting of 12 social indicators. This article also compares selected states on the basis of human development index (1981, 1991 and 2001) and SDI (2011) values. In addition, the study finds district-level SDI and ranks the districts of selected states, that is, Kerala, Haryana and Bihar. The findings of the study confirmed the northern–southern social development divide in India. The empirical findings show that Kerala is the best state among all states in India in terms of social progress. Results of the study confirmed huge disparities at district and states/UTs level in India.